Management and organizational innovation in Brazil: evidence from technology innovation surveys - Daniel Paulino Teixeira Lopes (Production, 2014)
From a broad perspective on the topic of innovation, considering not only technological innovations in products and processes but also management and organizational innovations, this study seeks to (1) discuss the main theoretical and conceptual approaches to innovation, especially management and organizational innovation; (2) understand how the subject has been studied since 1998 by the official innovation survey in Brazil (PINTEC); and (3) examine the evidence presented in three editions of the survey. The results show that innovation involves diverse phenomena and that there is a strong interrelation between technological innovation in products and processes and management and organizational innovations.